Measurement of executive functioning with the National Institute of Health Toolbox and the association to anxiety/depressive symptomatology in childhood/adolescence. Issue 6 (17th August 2020) - Kavanaugh, Brian C.; Cancilliere, Mary Kathryn; Fryc, Alexa; Tirrell, Eric; Oliveira, Jane; Oberman, Lindsay M.; Wexler, Bruce E.; Carpenter, Linda L.; Spirito, Anthony
ABSTRACT: Introduction: Despite preliminary research, there remain inconsistent findings with regard to the role of executive functioning (EF) deficits in childhood anxiety and depression. This report examined the association of The National Institute of Health (NIH) Toolbox to clinical neuropsychological measures and to childhood, anxiety/depressive symptomatology. Methods: One-hundred eight children and adolescents completed the three EF measures from the NIH Toolbox (List Sorting Working Memory Test [LSWMT], Dimensional Change Card Sorting Test [DCCST], and Flanker Test of Attention and Inhibition [Flanker]) in an outpatient neuropsychology program. These tests were compared to established measures of EF in terms of linear correlations and detection of impairment. Heaton's Global Deficit Score (GDS) was utilized to calculate impairment. The Toolbox-EF measures were paired with parent-reported EF symptoms (Behavior Rating Inventory of Executive Function [BRIEF2]) to identify the role of EF in childhood anxiety/depressive symptomatology. Results: Toolbox-EF measures displayed medium sized correlations with their clinically comparable counterparts, and generally did not differ in their detection of impairment. Toolbox-GDS was associated with depression diagnosis and clinically significant child-reported anxiety and depressive symptoms. Together, Toolbox/BRIEF2 accounted for 26.8–30.9% of elevated depressive symptom variance, but only 13.2-14% of elevated anxiety symptom variance. Further, EF impairment was associated with depression across self report, parent report, and clinical diagnosis. Discussion: The NIH Toolbox-EF measures display comparable psychometric properties to clinically available EF measures in a pediatric (primarily psychiatric) neuropsychology setting. The Toolbox appears to display an appropriate ability to detect EF deficits secondary to self-reported depression in childhood.